Pengetahuan Mahasiswa Terhadap Penggunaan kosmetik Non_BPOM di Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang - Siska Yohanifa; Siska Miga Dewi; Nurhasanah (Universitas Negeri Jakarta, 2023)
This research is based on the pre-review perception that emerged during the pre-study, identifying problems related to the lack of information among students at the Faculty of Tourism and Hospitality, Padang State University, about non-BPOM beauty care products. The reason for this research is to determine the degree of information of students at the Faculty of Tourism and Hospitality, Padang State University. The exploration philosophy used in this research is correlational with quantitative methodology. The population for this research is 724 students from the Faculty of Tourism and Hospitality at Padang State University, BP, in 2019. The examination procedure used is a purposive examination strategy with a sample of 82 people. The information collection strategy uses a survey. The information examination method uses SPSS 20. The results of the study show that students' knowledge of non-BPOM cosmetics is in the high category, namely 85.54%. This means that students have high knowledge about non-BPOM cosmetics at the Faculty of Tourism and Hospitality, Padang State University.